2022
DOI: 10.1039/d2ea00008c
|View full text |Cite
|
Sign up to set email alerts
|

Pre-monsoon submicron aerosol composition and source contribution in the Kathmandu Valley, Nepal

Abstract: The Kathmandu Valley in Nepal suffers from unhealthy air quality, with mean pre-monsoon submicron particulate matter concentration (PM1) of 40 µg m-3 and daily peaks over 75 µg m-3. A...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(30 citation statements)
references
References 139 publications
(286 reference statements)
5
25
0
Order By: Relevance
“…PM 2.5 and PM 10 concentrations at the two in-valley sites (Ratnapark and Lalitpur) were not significantly ( p = 0.33–0.34) different from each other but were significantly ( p < 0.001) higher than the more remote Dhulikhel site by a factor of 2.2–2.6 (Table ). Meanwhile, meteorological measurements, discussed and reported elsewhere, show similar conditions across the three sites, with slightly lower average temperature and relative humidity at Dhulikhel (7.8 °C, 67%, respectively) compared to Ratnapark (10.1 °C, 78%) and Lalitpur (11.2 °C, RH not available) . The average PM 2.5 concentrations at the in-valley sites (121–130 μg m –3 ) were similar to the average PM 2.5 concentrations observed in winter to spring of 2014 at six major roadways in the Kathmandu Valley (125 μg m –3 ) …”
Section: Resultssupporting
confidence: 77%
See 3 more Smart Citations
“…PM 2.5 and PM 10 concentrations at the two in-valley sites (Ratnapark and Lalitpur) were not significantly ( p = 0.33–0.34) different from each other but were significantly ( p < 0.001) higher than the more remote Dhulikhel site by a factor of 2.2–2.6 (Table ). Meanwhile, meteorological measurements, discussed and reported elsewhere, show similar conditions across the three sites, with slightly lower average temperature and relative humidity at Dhulikhel (7.8 °C, 67%, respectively) compared to Ratnapark (10.1 °C, 78%) and Lalitpur (11.2 °C, RH not available) . The average PM 2.5 concentrations at the in-valley sites (121–130 μg m –3 ) were similar to the average PM 2.5 concentrations observed in winter to spring of 2014 at six major roadways in the Kathmandu Valley (125 μg m –3 ) …”
Section: Resultssupporting
confidence: 77%
“…PM concentrations only had significant day/night variation at the Ratnapark site, where nighttime PM 10 concentrations were significantly ( p = 0.018) higher than the daytime concentrations. Meteorological measurements indicated semistagnant winds overnight (typically 0.5 m s –1 ) with a shallow boundary layer of ∼100 m depth compared to higher wind speeds during the day (1.5–2 m s –1 ) with a boundary layer of ∼800 m . Higher nighttime concentrations of PM in the Kathmandu Valley were observed previously at the Bode site and were explained by a shallower boundary layer, lower wind speed, cooler stagnant air, and favorable partitioning of gases to particles at higher relative humidity at night, especially for compounds with pH-dependent partitioning …”
Section: Resultsmentioning
confidence: 55%
See 2 more Smart Citations
“… 28 Other NAMaSTE papers involved with the source testing aspect of the campaign include Stockwell et al, who reported gas-phase emission factors and aerosol optical properties, and Jayarathne et al, 27 who reported off-line filter-based emission factors of fine aerosol (PM 2.5 ), organic carbon, elemental carbon, inorganic ions, organic molecular markers, trace metals, and PAHs. This work links the NAMaSTE source testing with ambient source apportionment work by Werden et al 30 that took place in the Kathmandu Valley in Nepal in 2015 and more recently. The AMS mass spectral profiles reported in this work are the first available for major undersampled sources in South Asia and important as such, but additional measurements could improve the representativeness or specificity available in the future.…”
Section: Introductionmentioning
confidence: 99%